Analyzing Growing Wood Pellet Markets in Face of Renewable Energy Demand: Making Informed Trading Decisions with Multi-Criteria Decision-Making Model - Bilgen Akmermer; Pelin Senturk (Drvna Industrija)
As a sustainable and cost-effective biofuel source for power generation and heating systems, wood pellets play a critical role in the renewable energy landscape. This leads to the discussion on their international trade on the edge of major global challenges such as climate change and energy security. In this paper, we focus on the wood pellets trade and analyze its growing markets by decision-making models. A hybrid multi-criteria decision-making model (MCDM) is proposed, supported by critical criteria of international trade, to trading countries’ executives to make informed decisions on target markets. The model includes both criteria (value imported, trade balance, unit value, annual growth in value, CO2 emission, logistic performance index, concentration of supplying countries) and alternatives (17 prior importing countries). It determines the weights of criteria by Criteria Importance Through Intercriteria Correlation (CRITIC) method and ranks alternatives by Additive Ratio Assessment (ARAS) technique. Based on CRITIC analysis, “concentration of supplying countries” is found as the most significant criterion. According to the results, within informed trading decisions, the top three markets for exporting countries are determined as the United Kingdom, Japan, and the Netherlands in terms of growing demand for wood pellets.